1994
DOI: 10.1002/ajh.2830460207
|View full text |Cite
|
Sign up to set email alerts
|

Use of alveolar carbon monoxide measurements to assess red blood cell survival in hemodialysis patients

Abstract: We recently described a simple technique for measuring RBC survival based on measurements of the concentration of carbon monoxide (CO) in alveolar air, corrected for environmental CO using a device that equilibrates with atmospheric CO at the same rate as does the patient. The purpose of the present report is to demonstrate the clinical utility of this method via measurements of RBC turnover in hemodialysis patients. Prior to dialysis, the mean RBC survival of 9 chronic dialysis patients was 70 +/- 9 days, abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 21 publications
(8 reference statements)
1
30
1
Order By: Relevance
“…3 Erythrocyte sodium sensitivity (ESS) measured before 4h-hemodialysis. The dotted horizontal line indicates the ESS reference value (=4.3) obtained in a previous study [7]. ESS values below the dotted line (green columns) indicate patients with low salt sensitivity, ESS values above the dotted line (red columns) indicate the opposite. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Erythrocyte sodium sensitivity (ESS) measured before 4h-hemodialysis. The dotted horizontal line indicates the ESS reference value (=4.3) obtained in a previous study [7]. ESS values below the dotted line (green columns) indicate patients with low salt sensitivity, ESS values above the dotted line (red columns) indicate the opposite. …”
Section: Resultsmentioning
confidence: 99%
“…Most likely this is caused by a mechanical interaction between RBC and vessel wall due to insufficient repulsive forces between the erythrocytes and the endothelial cell surface [8]. In the early days of hemodialysis mechanical destruction of erythrocytes during frequent hemodialysis was thought to be a major cause for anemia observed in these patients [7,8,9,10,11,12,13,14,15,16,17,18]. Along with the technical improvement of the dialysis equipment the adverse (mechanical) influence of the dialysis process by itself on erythrocyte survival became less [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medina et al . have shown that the dialysis procedure led to a 20% increase in RBC destruction, measured by an increase in carbon monoxide concentration in alveolar air during treatment [72]. Fluid removal during the HD treatment leads to diminished flow in the microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of uremic toxins, excessive toxic storage of aluminium in the bone marrow (Miyoshi, 2006), blood loss (either iatrogenic, from the puncture sites of the vascular access and blood sampling, or from other sources, such as the gastrointestinal tract), and premature erythrocyte destruction have also been frequently associated with anaemia in stage 5 CKD patients (Medina, 1994;Pisoni, 2004).…”
Section: Introductionmentioning
confidence: 99%